The Imaginary of Wild Nature in the Trips to Chile Narrated in Orizzonte mobile and Croce del sud. Tre vite vere e improbabili (Altre Modernità, 2025)
The present essay intends to investigate the updates of an imaginary that still enjoys much popularity in the Italian literary scene: the imaginary of wild nature. Such imaginary will be analyzed in Orizzonte mobile by Daniele Del Giudice (2009) and Croce del sud. Tre vite vere e improbabili by Claudio Magris (2020), novels that could be placed within the most successful literary phenomenon of the last decades, according to Westphal and Brevini, not only in Italy, but also in the rest of Europe: that of geographical fictions or exotic adventure novels. The hypothesis of the essay posits that spatial representations of Chile are carried out through an ambivalent perspective that coincides with that of the romantic tourist (Urry 1990; Leed 1992; Bonadei 2007; Urry and Larsen 2011), a contradictory figure who likes to preserve the imaginary of wild nature, but at the same time gets rid of it by proposing new configurations of meaning. The aim will be to examine the literary procedures with which the imaginary of wilderness is strained. These are: generalization, intertextuality, the asyndeton and the comparison, mechanisms that are recurrently used to refer to wilderness, either preserving its traditional ideologies or innovating them.
Keywords: imaginary of wild nature; representation of Chilean spaces; contemporary Italian narrative; fictional geographics